Colours of the high country : exploring place through colour : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand - Johnstone, Kristy (Massey University, 2012)
In an age when digital colour and ready-made colour charts have resulted in the loss of the tactile qualities of colour this project investigates how colour can authentically represent place. New Zealand merino has been given a stronger identity when the product is able to be traced back to the farm gate. Using the concept of terroir, a French term used in the wine industry suggesting that the flavour of wine is affected by the land and the climate where it is produced, I have sought to find a visual terroir through the material nature of colour by using dye extracted from vegetation physically collected from actual places and applying it to merino wool. Colours extracted from these plants are affected by the characteristics of each place resulting in tactile colours forming an individual colour palette unique to each sheep station with meaning and content embedded in them. My role has been to extract and interpret the colours in such a way as to allow the vegetation to reveal the truth of that place through colour. This colour, which is inherently connected to its origins, brings further integrity to the story of New Zealand wool.
Keywords: New Zealand wool; Plant dyes; Merino wool; Natural colour; Terroir